Termination Of Employment Upon Change In Ownership Of Business - Ahmad, Sharifah Suhana (Journal of Malaysian and Comparative Law, 2019)
Once upon a time an employee enjoyed the freedom to enter into a contracrt of employment with an employer of his choice. The common law declared that should there be a change of employer, an employee's service could not be transferred to the new employer without his consent. If an employee could not exercise this freedom of choice his status would be relegated to that of a slave. However, the judicial pronouncement which championed the rights of employee as human beings to choose for whom they wished to labour was found to eventually work against them. Freedom of contract works both ways: while an employee may decide to continue to work for the new employer, the new employer may decide to exercise his right not to employ him.